Differences in Stress Levels Due to Dental Pain based on Age Group in the Working Area of Jelbuk Jember Health Center - Ristya Widi Endah Yani; Kiswaluyo; Emi Wuri Wuryaningsih; Firdausi Ramadhani; Pungky Amelia Purwoko Putri (Journal Of Nursing Practice, 2026)
Background: Stress caused by dental pain is a common but overlooked issue affecting all age groups. The health profile of Jember Regency in 2023 recorded that there were 94,439 cases of dental problems occurred in Jember Regency, with Jelbuk District ranking third in caries prevalence. This is exacerbated by the low number of visits to dentists in Jelbuk District, resulting in toothaches not being treated immediately, which can cause serious problems in the form of stress. Purpose: This study was conducted to determine differences in stress levels due to dental pain based on age groups in the working area of Jelbuk Jember Health Center. Methods: The methodology used in this study was observational analytic with a cross-sectional approach involving 120 people consisting of children, adolescents, adults, and the elderly selected through a purposive sampling technique. Variables in this study were stress levels due to dental pain and age.  Data were analyzed using IBM SPSS Statistics version 31.0 with Kruskal–Wallis and Mann Whitney test. Results: The results showed that subjects who experienced more mild stress were children (86.7%) and adolescents (66.7%), then subjects who experienced more moderate stress were adults (46.7%), and subjects who experienced more severe stress were elderly (36.7%). Analysis of the data obtained shows P-Value=0,000, meaning that there are differences in stress levels due to dental pain between age groups. Conclusion: In conclusion, children with adults, children with the elderly, adolescents with the elderly, and adults with the elderly show differences in stress levels due to dental pain, while children with adolescents and adolescents with adults do not show any differences in stress levels due to dental pain.